Bioactive glasses materials, properties and applications - Ylanen, Heimo O. (Elsevier, 2018)
Bioactive Glasses: Materials, Properties and Applications, Second Edition provides revised, expanded and updated content on the current status of this unique material, including its properties, technologies and applications. The book is suitable for those active in the biomaterials and bioengineering field, and includes eight new chapters that cover material types, computational modeling, coatings and applications. Chapters deal with the materials and mechanical properties of bioactive glass and the applications of bioactive glasses, covering their uses in wound healing, maxillofacial surgery and bone tissue engineering, among other topics. With its distinguished editor and expert team of international contributors, the book is an invaluable reference for researchers and scientists in the field of biomaterials, both in academia and industry.--Provided by publisher.